Effect of infection on food intake and the nutritional state: perspectives as viewed from the village - Mata Jiménez, Leonardo (1977)
Data from a prospective study of a Guatemalan village population revealed an exceedingly high force of infection which may affect nutrition and growth from gestation onward. Maternal morbidity was higher and fetal antigenic stimulation was more frequent than in industrial societies. Infection of the young child was a common occurrence and, although a great many infections were silent, morbidity rates were extremely high, particularly during the protracted weaning period (6 to 24 months). Infectious disease was found to be an important cause of weight loss, arrest in height, and impaired physical growth. Also, it was a common precipitating factor of severe malnutrition and death. Analysis of the dietary data of fully weaned children did not reveal a deficit in protein intake. Most children, however, had very low calorie intakes. Infectious disease was a common cause of anorexia and of marked reduction in calorie intake, followed by weight loss and impaired physical growth. A strong inverse correlation was detected between infectious disease and calorie intake in the 2nd year of life, when children were being weaned. Infection is the most important isolated factor in the causation of malnutrition in the village. A reorientation of health and nutrition policies seems in line in view of failures of food supplementation programs, particularly with protein, in many parts of the world.